Fuzzy Logic Control System in Medical Field - Zermane Hanane (Proceedings of the International Conference on Industrial Engineering and Operations Management, 26-27 July Paris, France, 2018)
Since the work of Lotfi Zadeh in 1965, the fuzzy logic continues to interest researchers and industrialists who gather around the "theories of uncertainty". The ramifications of fuzzy logic extend to fields as varied as control, the diagnosis of complex systems, bioinformatics, decision support. Research work is done in bio-informatic field where a system for decision support of anesthetic depth fuzzy basic. This study was carried out under general anesthesia with propofol. We use in our work some parameters influencing the patient's condition during the course of surgery to control their effects on the depth of general anesthesia by fuzzy logic. In this paper, we propose using the environment MatLab R2017a to realize this application. A comparison between the predictions of the anesthesiologist and anesthetic predictions according to fuzzy logic of our work is done. This study will serve as a guide in developing new anesthesia control systems for patients.